Sketches from a Young Country : The Images of Grip Magazine - Cumming, Carman (Book collections on Project MUSE., 1997)
Sketches from a Young Country is the first comprehensive study to evaluate this historically important magazine, to assess the motivations of its authors, and to set both in social and political context. Containing over a hundred of Bengough's cartoons, with captions to clarify contemporary references, and offering an assessment of Grip in relation to its British and American counterparts, Sketches from a Young Country makes an exciting contribution to popular history, Canadian politics, and the history of journalism.